Communication Form Of Tungku Tigo Sajarangan As Minangkabau Leader (Study in Nagari Sungai Abu, SolokRegency, West Sumatra) - Sintia Hariani Wirianti; Hoirul Anam (ASTEEC, 2023)
This research focuses on the Sungai Abu community as an ethnic Minangkabau who is bound by the laws that apply in society. Because the penghulu acts as a leader and traditional leader, Cadiak Pandai is a person who is intelligent/scientist, scholar, bureaucrat, politician, scientist and expert in various professions, while Alim Ulama is a person who is an expert in religion and religious leaders. Through the library research method used, by collecting data through journal articles, related books, and reading several previous studies, the author observed Tigo Sajarangan Tungku's form of communication in leading in Nagari Sungai Abu. Among them contains three aspects. First, communicating in the realm of deliberation and consensus as a means of decision making. Second, communicating by establishing functional integration to preserve the customs of the Abu River. Third, communicate using figures of speech as a form of polite language in speaking and conveying ideas.